One hundred years of national capital-making: The case of Bratislava, Slovakia - Buček, Ján; Plešivčák, Martin; Bačík, Vladimír (Quaestiones Geographicae, 2024)
Although Bratislava is one of the youngest national capital cities in the world, we can observe a much longer process of its capital-making. We document its gradual formation as a centre of national politics and government, as well as the centre of national culture and national symbol. Bratislava confirms the impact of assumptions and experiences as a sometimes-interim capital city and regional capital within Czechoslovakia. Facing a sudden takeover of the national capital function, we document the process of national capital-making from 1993 in more detail. There were various obstacles in key political, governmental and cultural institution-building. They are demonstrated by their headquarters location search and development, as well as in the context of interurban competition. We argue that Bratislava has already concentrated the majority of political and cultural centre functions of the state capital, despite historical turbulences and accompanying constraints. We identify their location patterns and illustrate their impact on the urban physical development of the city.